Efficacy and safety of transarterial chemoembolization plus sorafenib in patients with recurrent hepatocellular carcinoma after liver transplantation - Zhang, Xia; Cai, Lirong; Fang, Jian; Chen, Fengsui; Pan, Fan; Zhang, Kun; Huang, Qian; Huang, Yuju; Li, Dongliang; Lv, Lizhi; Chen, Man; Yan, Ruiying; et al. (Frontiers in Oncology, 2023)
Objectives To explore the benefit and safety of transarterial chemoembolization (TACE) in combination with sorafenib in patients with recurrent hepatocellular carcinoma (HCC) after orthotopic liver transplantation (OLT). Methods In this multi-center retrospective study, 106 patients with recurrent HCC after OLT were included. Fifty-two patients were treated with TACE plus sorafenib (TS group) and 54 were treated with TACE alone (TC group). Primary and secondary endpoints including overall survival (OS) and progression-free survival (PFS), and safety were assessed. Results The median OS (17 vs 10 months, P=0.035) and PFS (12 vs 6 months, P=0.004) in the TS group were longer than those in the TC group. On multivariate analysis, BCLC stage (HR [hazard ratio]=0.73 [95% CI, 0.27–0.99], P=0.036) and sorafenib medication (HR=2.26 [95% CI, 1.35–3.69], P=0.01) were identified as independent prognostic risk factors for OS. No severe adverse events related to sorafenib were noted in the TS group. Four patients discontinued sorafenib due to intolerance. Conclusion TACE in combination with sorafenib is a feasible regimen to improve the survival with mild toxicity in patients with recurrent HCC after OLT.